Delivery of Islamic Da’wah Through Instagram Reels on The @Adihidayatofficial Account Towards Teenagers' Awareness in Reading the Quran - Istiqomah, Dhia; Zulfa Al Muthoharoh; Aatina Khairal ‘Athiyyah Zen; Yusnani; Nasrulloh (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
Many teenagers suffer losses because they are reluctant to read the Quran and are more immersed in the world. This research was carried out to determine the delivery of Islamic da’wah through Instagram reels on the @adihidayatofficial account regarding teenagers' awareness of reading the Quran. The method used in this research is a qualitative method with a descriptive approach. The data sources for this research are documents, video reels posted by Ustadz Adi Hidayat's Instagram account (@adihidayatofficial). Data analysis in this research is connected to relevant theories and is related to dawah media, da'wah messages, and also new media. The results of this research are that there are three pieces of evidence that Islamic da’wah through Instagram reels on the @adihidayatofficial account are able to provide awareness to teenagers in reading the Quran, namely the urgency of Islamic da’wah on Instagram social media, the existence of naqli and aqli arguments, and Ustadz Adi Hidayat's Instagram reels.